Représenter Austerlitz : le système icono-textuel napoléonien - Denis, Béatrice (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2022)
This article examines how the battle of Austerlitz (December 2, 1805) became a symbol of Napoleonic power. It argues that this happened through deliberate propaganda efforts, with a carefully crafted written version of the events leading to the battle, found in the 30th bulletin de la Grande Armée, as well as three paintings commissioned by Napoleon in March 1806, not long after the close of the successful 1805 campaign. The fame of the battle was forged by Napoleon himself by way of a text/image system that constructs its own authority and veracity. The images commissioned and created repeat what was read in the bulletin in different genres. The bulletin and the three paintings, by Louis-François Lejeune, Louis-Albert-Guislain Bacler d’Albe, and François Gérard successfully work together to sanction a unique version of events intended for posterity, one in which the eve of the battle occupies a prominent place.